Myrcia macrocalyx (Myrtaceae), a new species from Brazil, with additional morphological highlights - Faria, Jair Eustáquio Quintino; Gomes-Bezerra, Kadja Milena; Zanatta, Maria Rosa Vargas; Silva Júnior, Manoel Cláudio; Soares-Silva, Lucia Helena (Phytotaxa, 2015)
Myrcia macrocalyx, a new species from Cavalcante, Goiás, Brazil, is here described and illustrated. Additional details on the leaf architecture, geographical distribution, and conservation status of this species are also provided.